Development of Rubric of Attitude Assessment of Writing Explanation Text Based on Information Literacy on 11th Grade Students of Vocational High School Pencawan Medan - Suriya Emanita Br. Karo; Mutsyuhito Solin; Abdurahman Adisaputera (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to produce an attitude assessment rubric product in the form of an attitude assessment rubric handbook on writing explanation text material and knowing the process of developing and the feasibility of the product. This research method is a method of research and development Research and Development (R & D). Data is collected through validation of material experts and evaluation experts, the response of Indonesian teachers in Medan Pencawan SMKS and 35 class XI SMK students as research subjects. Data collection in the form of questionnaire assessment. The analysis is done by changing quantitative data into qualitative data using a Likert scale. The product evaluation in the form of a guide book on attitude assessment rubrics by material experts shows that the presentation of the suitability of the task material with KI and KD is 88% in the excellent category, the language and writing rubric attitude assessment is 97% in the excellent category, the learning activities of students have a percentage of 94% with a very good category, and supporting material has a presentation of 88% with a very good category. The overall average is 92% in the excellent category. The attitude rubrics assessment book by attitude evaluation experts with an overall average of 96% falls into excellent category. The attitude assessment handbook rubric assessment by Indonesian language teachers has an average total percentage of 89% with the criteria of "Excellent". In the test results the use of pretest with an average value of 73.17 and posttest with an average value of 80.48.